Leaving no woman or girl behind? Inclusion and participation in digital maternal health programs in sub-Saharan Africa - Ogochukwu Udenigwe; Sanni Yaya (BMC, 2022)
Abstract Across sub-Saharan Africa where access to adequate maternal healthcare is fraught with myriad challenges, especially for hard-to-reach populations, digital health technologies offer opportunities to improve maternal health outcomes. Digital health can circumvent inefficiencies in the traditional healthcare system and address challenges such as limited access to in-person medical consultations, and poor access to skilled birth attendants and health promotion activities. These benefits notwithstanding, digital health can be exclusionary. Too often, digital maternal health programs are not designed with a focus on equity in distribution nor are they designed from a gender equity standpoint. In this paper, we illustrate exclusionary practices of digital health programs through an extensive literature review of digital maternal health programs across sub-Saharan Africa. Taking an intersectional approach, we discuss how women are most vulnerable and excluded at the intersection of gender, literacy, and disability. Tackling exclusionary practices in digital health is crucial to ensure that no woman or girl is left behind.